PEMBACAAN SEMIOTIK TERHADAP PUISI “LAGU DARI POJOK JALANAN” KARYA SONI FARID MAULANA (KAJIAN SEMIOTIK RIFFATERRE) - Eri Rahmawati (Universitas Sultan Ageng Tirtayasa, 2016)
This research is aimed at finding out the wholistic meaning of the poem “Lagu dari Pojok Jalanan” by Soni Farid Maulana. The theory of semiotics from Michael Riffaterre was applied to find it. The poem was chosen since it represents “Reformation Era.” This era is the initiation of a big change in the government and social order of Indonesia by the succession of Soeharto as Indonesian President. The analysis was done through some processes; heuristic and hermeneutic reading, finding the matrix, model, and variants. The analysis revealed that the wholistic meaning of the poem: Indonesians were not truly free though they have gained their sovereignity from Janapanese colonialism from a very long time. It can be seen from the flaming of economic, political, and social state. There were still many chaoses, fire in the cities and forests, expensive prices, etc., resulting in the end of a periode of power.